Keragaman dan Pengelompokan Sumber Daya Genetik Kacang Tunggak [Vigna unguiculata (L.) Walp.] - Trustinah, Trustinah; Kasno, Astanto; Mejaya, Made Jana (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Cowpea [Vigna unguiculata (L.) Walp.] is a legume that  tolerant to drought and acid soil, that is prospective for development in sub-optimal area. A total of 150 cowpea accessions were grown at Muneng Research Station (Probolinggo) in dry seasson of 2014, using a randomized block design, with two replications.  Each accession were planted along  two rows of 4 m. The accession was varied for the qualitative and quantitative traits. Most of the accession had ovate leaf shape, flower color purple,  cream color of mature pod, and seed color brown to yellowish. Seed yield had a high phenotipic and genotypic coefficient of variation and genetic advance.  Low of phenotipic and genotypic coefficient of variation were shown on days to 50% flowering and days to physiological maturing.  Characteristics of cowpea accessions for eight variables 64.2% can be explained by three factors. The first factor relates to seed yield component (number of fertile nodes, number of branches, and seed weight), second factor associated with plant age (date of flowering and harvesting), and the third factor is the supporting factors (plant height, pod length, and number of seeds per pod). Accessions of cowpea could be divided into three groups. Date of flowering and harvesting were a determinant variable discriminant function. Group I consisting  70 accessions dominated by accessions with early maturity, medium plant height,   long pods, high number of seeds per pod and high seed yield.  Group II consisting of 47 accessions with moderate maturity, short plants, short pods, low number of seeds per pod and low seed yield. Group III consisting of 33 accessions was characterized by moderate maturity, high plant, short pods, high number of seeds per pod and high seed yield.